The correct name for the New Zealand endemic conifer Hall’s totara (Araucariales: Podocarpaceae) - Molloy, Brian (Phytotaxa, 2015)
Podocarpus laetus is the earliest available legitimate name for the New Zealand conifer Hall’s totara, presently known as P. hallii or P. cunninghamii. The status of these two names is discussed, and the background of P. laetus and species it has been associated with are reviewed. The name P. laetus is reinstated and typified.